Manajemen Pembiayaan Berbasis Nilai Syariah Dan Kinerja Bank Syariah Tinjauan Literatur - Marunta, Ristiyanti Ahmadul; Fatrisia, Anggun Ade; Hirmayani, Amanda; Hasniar; Herni; Aulia, Malika Kesya (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This research aims to examine the concept of sharia values in sharia banking, its integration mechanisms in financing management, as well as the influence of sharia value-based financing management on the performance of sharia banks. The research approach used is qualitative with a literature review method of various national journals and relevant scientific proceedings. Data was collected through literature searches on scientific databases such as Google Scholar and accredited national journal portals, then analyzed using systematic content analysis techniques. The results of the study show that sharia values such as monotheism, justice, trust, transparency, benefit and balance are the fundamental basis for sharia bank operations and differentiate them from conventional banking. The integration of these values in financing management is realized through the use of sharia contracts, application of the precautionary principle, compliance with sharia fatwas, and orientation to sharia maqashid. Sharia value-based financing management has been proven to have a positive effect on the performance of sharia banks, both from the financial, operational, risk management and non-financial performance aspects from a sharia maqashid perspective. Thus, strengthening the integration of sharia values in financing management is a strategic factor in improving the performance and sustainability of sharia banks.